Penggunaan Donna Harun Sebagai Endorser Iklan di Televisi dan Pengaruhnya Terhadap Keputusan Pembelian Citra Lasting Youth Hand&Body Lotion (Studi Pada Konsumen di Kelurahan Wates Mojokerto) - Wilujeng, Novie; Andjarwati, Anik Lestari (BISMA (Bisnis dan Manajemen), 2018)
Indonesia is a potensial market for the product cosmetology and body treatmen. This can be seen from hundreds of cosmetic brand offered to consumers. Consumers' mind at this time has been met by a variety of ad products that beauty comes through television, radio and news media. In order for consumers to be interested to purchase products that advertising one of the ways used by the manufacturer is using a celebrity as endorser. Celebrity credibility, celebrity and brands mathcup, celebrity and audience mathcup, and the attractiveness of celebrities expected to make consumers purchase decisions.This research is conclusive research use multiple regression analysis. The sample used in this research was 103 people, which is the consumer Citra in Wates Mojokerto Distric. Research aims to understand Aplication of Dona Harun as Advertising endorser in Televition and Influence to Buyying Decision citra Lasting Youth hand&Body Lotion (Study at Consumer in Wates Mojokerto Distric) This research is shown determination coefficient (Adjusted R2) or 51% it means, there is influence simultaneously between using celebrity is advertising endorser in televition to buying decision Credibility it means variabel is more dominant in influence buying decision and followed by other variabel (attractiveness, celebrity and brand mathcup, and celebrity and audience matchup) Suggested to the researchers to do further research outside the free variables used in this research, so that insight abauot marketing communication and purchasing decision become more knowledgeabele